Fetal programming and gestational diabetes mellitus. (December 2016) - Monteiro, Lara J.; Norman, Jane E.; Rice, Gregory E.; Illanes, Sebastián E.
Abstract: Gestational diabetes mellitus is defined by new-onset glucose intolerance during pregnancy. About 2–5% of all pregnant women develop gestational diabetes during their pregnancies and the prevalence has increased considerably during the last decade. This metabolic condition is manifested when pancreatic β-cells lose their ability to compensate for increased insulin resistance during pregnancy, however, the pathogenesis of the disease remains largely unknown. Gestational diabetes is strongly associated with adverse pregnancy outcome as well as with long-term adverse effects on the offspring which likely occurs due to epigenetic modifications of the fetal genome. In the current review we address gestational diabetes and the short and long term complications for both mothers and offspring focusing on the importance of fetal programming in conferring risk of developing diseases in adulthood. Highlights: Gestational diabetes prevalence is increasing globally. Fetal programming predisposes for future diseases in diabetic mothers and offspring. Need to stablish perinatal management and postpartum diabetes prevention strategies. Long term complications could be predicted by early-pregnancy diagnostic models for GDM.